Future trajectories of change for an Arctic deep‐sea ecosystem connected to coastal kelp forests. (11th January 2021) - Vilas, Daniel; Coll, Marta; Pedersen, Torstein; Corrales, Xavier; Filbee‐Dexter, Karen; Wernberg, Thomas
Abstract : Environmental stressors related to climate change and other anthropogenic activities are impacting Arctic marine ecosystems at exceptional rates. Within this context, predicting future scenarios of deep‐sea ecosystems and their consequences linked with the fate of coastal areas is a growing need and challenge. We used an existing food‐web model developed to represent the outer basin of the Malangen fjord, a northern Norwegian deep‐sea ecosystem, to assess the potential effects of plausible future trajectories of change for major drivers in the area, including links to coastal kelp forests. We considered four major drivers (kelp particulate organic matter [POM] production entering the deep sea, fishing effort, king crab invasion, and ocean warming) to project 12 future scenarios using the temporal dynamic module of Ecopath with Ecosim approach. Overall, we found that the impact of warming on the deep‐sea ecosystem structure and functioning, as well as on ecosystem services, are predicted to be greater than changes in kelp forest dynamics and their POM production entering the deep sea and the king crab invasion. Yet, the cumulative impacts are predicted to be more important than noncumulative since some stressors acted synergistically. These results illustrate the vulnerability of sub‐Arctic and Arctic marine ecosystems to climate change and consequently call for conservation, restoration, and adaptation measures in deep‐sea and adjacent ecosystems. Results also highlight the importance of considering additional stressors affecting deep‐sea communities to predict cumulative impacts in an ecosystem‐based management and global change context and the interlinkages between coastal and deep‐sea environments.